Tracking the sources of psychrotrophic bacteria contaminating chicken cuts during processing. (August 2019) - Samapundo, S.; de Baenst, I.; Aerts, M.; Cnockaert, M.; Devlieghere, F.; Van Damme, P.
Abstract: The major aim of the study was to establish the routes via which spoilage associated psychrotrophic bacteria contaminate poultry products at a large processing plant located in Belgium. Environmental samples were collected consisting of samples of air and swabs of food contact surfaces. Product samples were also collected consisting of modified atmosphere packaged (MAP) chicken wings and legs, which were analyzed microbiologically on the same day they were produced as well as after their sell-by date. Psychrotrophic bacteria from these samples were subsequently clustered and identified by means of MALDI-TOF MS and 16S rRNA gene sequencing. Carnobacterium maltaromaticum was determined to dominate the spoilage flora of both wings and legs. Other psychrotrophic bacteria able to grow on MRS which were identified on expired wings and legs included Carnobacterium divergens, Brocothrix thermosphacta, Lactobacillus curvatus, and Lactobacillus brevis . These were determined to arise from food contact surfaces such as cutting blades, leg hooks, Ertalon and polyurethane conveyor belts, working tables, and the hands of the operators. Importantly, it was determined that cleaning and disinfection was largely inadequate. Air was also determined to be an important vector of psychrotrophic bacteria in the processing environment, potentially contaminating the products directly or indirectly. Highlights: Sources of psychrotrophic bacteria were determined at a poultry processing plant. Clustering and identification was by MALDI-TOF MS and 16S rRNA gene sequencing. Carnobacterium maltaromaticum dominated the spoilage flora of both wings and legs. Spoilage associated psychrotrophs largely arise from food contact surfaces. Air is important vector of psychrotrophic bacteria in the processing environment.